Incidence of thrombosis in relapsed/refractory B-cell lymphoma treated with axicabtagene ciloleucel: Mayo Clinic experience. Issue 6 (12th May 2022) - Melody, Megan; Gandhi, Sangeetha; Saunders, Hollie; Abdel-Rahman, Zaid; Hastings, Jacquelyn; Lengerke Diaz, Paula; Gannon, Nicole; Truong, Tuan; Hathcock, Matthew; Khurana, Arushi; Johnston, Patrick; Ansell, Stephen; et al.
Abstract: Chimeric antigen receptor (CAR) T-cell therapy is effective in relapsed/refractory large B-cell lymphoma and results in a unique toxicity profile, namely cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome. The hyper-inflammatory state associated with these toxicities has been suggested to increase the risk of thrombosis. We conducted a retrospective analysis of patients treated with axicabtagene ciloleucel (axi-cel) to assess the rate of thrombosis with axi-cel therapy from the time of CAR T-cell infusion until the end of hospitalization, when performed in the inpatient setting, or up to day +30 when performed in the outpatient setting. Ninety-two (95%) of 97 patients were hospitalized during axi-cel therapy and 85 (88%) developed CRS. Fifty-five patients (57%) received concurrent anticoagulation (53 as prophylaxis). Patients with prior VTE did not have progression or evidence of new VTE. Only 2 (2.1%) patients developed VTE. These results demonstrate a low-risk for thrombosis in axi-cel recipients.